Between Ḍarūrah and Halal Integrity: MUI Fatwas on Harm-Derived Vaccines and Medicines - Muhammad Amin, Abd. Rauf; Syatar, Abdul; Abubakar, Achmad; Kurniati, Kurniati; Alimuddin, Harwis (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This article aims to uncover emergency considerations in the halalness and hygiene of vaccines and medicines made from harm ingredients. This study is qualitative research using the darūrah concept approach by Wahbah al-Zuhailī. A darūrah approach to analyzing the needs of the Indonesian people for vaccinations and needed medicines. The data analyzed comes from literature and such as articles, books and the views of scholars. The results of the study found that in the MUI fatwa products on vaccination products and medicines there are different legal provisions, vaccines are considered halal and pure, which is very appropriate by considering the aspects of emergency in the teachings of Islamic law. Unlike the medicine made from pork gelatin, MUI forbids it because it is not included in istihālah. So that the MUI fatwa product has a significant influence in awakening Muslims in Indonesia to be careful in determining vaccines and medicines used. The implication is that the emergency consideration in terms of protecting the soul (hifẓ al-nafs) is personal for the perpetrators of vaccinations and medicines, their families, the wider community, and citizens of the world. This effort is the highest-level solution in terms of protecting the soul (hifẓ al-nafs) in maqāṣid sharī'ah terms. The hope of the fatwa is to try to provide a complex understanding to the public so that they believe that the raw materials of vaccine and medicine products are important to be considered halal and holy so that the public trusts all elements involved. In this way, that people also feel legally confident about the drugs they are using because their legal status is clear.